Cloud Computing Access Control Using Blockchain - Alshammari, Manal Ayyadh; Hamdi, Hedi; Mahmood, Mahmood A.; El-Aziz, A. A. Abd (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Access control is a pivotal aspect of modern computing systems, ensuring that only authorized entities can interact with sensitive data and resources. Traditional access control methods, while effective, face challenges in terms of security, transparency, and scalability. Blockchain technology has emerged as a promising solution to enhance access control in cloud computing environments. Blockchain's inherent features, such as decentralization, immutability, and cryptographic security, offer a unique framework for addressing the limitations of traditional access control systems. In this paper, we explore the integration of blockchain technology with cloud computing to establish a more secure and transparent access control mechanism. By utilizing blockchain, access control policies and permissions can be stored in a tamper-proof and transparent ledger. Scalability is an issue since processing many access control transactions on the blockchain might cause network congestion and sluggish processing. Transactions take time to upload to the blockchain, which can delay real-time access choices. It takes skill to integrate and manage blockchain and cloud technologies together. Choosing the correct consensus mechanism affects system efficiency and security. Consider the costs of establishing and maintaining such a system and the difficulty of fixing faults owing to blockchain immutability. In conclusion, this paper underscores the significance of access control in cloud computing and the limitations of traditional approaches. By harnessing the power of blockchain technology, a more secure, transparent, and scalable access control framework can be established, revolutionizing the way we manage access to sensitive data and resources in complex digital ecosystems.